2013
DOI: 10.1167/iovs.13-12981
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization of Perforating Vessels and Focal Scleral Ectasia in Pathological Myopia

Abstract: We showed that perforating vessels are localized at the border/bottom of focal scleral ectasia in pathologic myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Perforating scleral vessels have been implicated in the pathogenesis of structural changes of the sclera as investigated by OCT and reported by Pedinielli et al 10 and Ohno-Matsui et al 11 More recently, Querques et al 12 reported on the formation of lacquer cracks in pathologic myopia. Assessed by indocyanine green angiography angiography, Moriyama et al 18 found a lower number of PCAs and a displacement of the entry site in highly myopic eyes compared with controls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Perforating scleral vessels have been implicated in the pathogenesis of structural changes of the sclera as investigated by OCT and reported by Pedinielli et al 10 and Ohno-Matsui et al 11 More recently, Querques et al 12 reported on the formation of lacquer cracks in pathologic myopia. Assessed by indocyanine green angiography angiography, Moriyama et al 18 found a lower number of PCAs and a displacement of the entry site in highly myopic eyes compared with controls.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple sectorial watershed zones meet in the submacular region, presumably making the macula and the avascular zone of the fovea vulnerable to ischemia under certain conditions. 9 Perforating scleral vessels (PSVs) have been visualized as linear hyporeflective structures at the level of the sclera by EDI-SDOCT and swept-source OCT in pathologic myopia as reported by Pedinielli et al 10 and Ohno-Matsui et al 11 More recently, perforating scleral vessels have been investigated in connection with lacquer cracks in pathologic myopia by Querques et al 12 They have been hypothesized to act as "locus minoris resistentiae," leading to scleral expansion and lacquer crack formation. Because of low signal-to-noise ratio, the visualization of PSVs in emmetropic eyes has been more problematic to date.…”
mentioning
confidence: 88%
“…We have characterized SCP as a novel OCT finding in patients with choroideremia, which are discrete fovea-sparing lesions that involve the macula, and appear as dramatic structural defects of the sclera, and to varying degrees, Bruch’s membrane, the RPE, and retina. The spectrum of SCP in choroideremia appear phenotypically different from those typically found in pathologic myopia that are characterized as a posterior thinning and out-pouching of the scleral on OCT. 25,26 However, some SCP in choroideremia resemble the peripapillary lesions in pathologic myopia as described by Ohno-Matsui and colleagues. 27 In addition, Ohno-Matsui et al also showed that short posterior ciliary arteries (SPCA) penetrate the eye at the sites of SCP, which is similar to our findings in choroideremia.…”
Section: Discussionmentioning
confidence: 92%
“…Moriyama et al 18 showed displaced PCAs entrance in the choroid around the boundaries of the staphyloma. Pedinielli et al 7 showed PCAs in the border of focal ectasia. However, in high myopia, the sclera is thin so that superficial PCAs could be mistaken for SPCAs because of the high remodeling of the choroid, sclera, and scleral vessels.…”
Section: Discussionmentioning
confidence: 97%
“…6 There have been previous reports showing perforating vessels using OCT in myopes. 7,8 However, previous reports analyzed spectral domain OCT over a smaller area 9 .…”
Section: Introductionmentioning
confidence: 99%